Intrabone Transplant of Cord Blood Stem Cells Establishes a Local Engraftment Store: A Functional PET/FDG Study. (2nd October 2012) - Marini, Cecilia; Podestà, Marina; Massollo, Michela; Capitanio, Selene; Fiz, Francesco; Morbelli, Silvia; Brignone, Massimo; Bacigalupo, Andrea; Piana, Michele; Frassoni, Francesco; Sambuceti, Gianmario
Abstract : Background . Despite advancements in comprehension of molecular mechanisms governing bone marrow (BM) homing of hematopoietic stem cells, cord blood transplant (CBT) suffers from a slow rate of hematopoietic recovery. Intrabone (IB) injection has been proposed as a method able to improve speed of BM engraftment with respect to conventional IV protocols. However, the mechanisms underlying this benefit are largely unknown. Aim . To verify whether IB-CBT determines a local engraftment able to predict the reconstitution of recipient hematopoiesis. Design and Methods . Twenty-one patients with hematologic malignancies received IB injection into both iliac crests of3.2 ± 0.68 * 107/kg cord blood cells. One month following IB-CBT, PET-CT imaging was performed. Maximal standardized uptake values (SUVs) were assessed in BM of both iliac crests and in all lumbar vertebrae. Results . Maximal SUV within iliac crests was higher than in lumbar vertebrae (4.1 ± 1.7 versus3.2 ± 0.7, resp., P = 0.01 ). However, metabolic activity in these two different BM districts was significantly correlated (r = 0.7, P < 0.001 ). Moreover, FDG uptake values within the injection site closely predicted platelet recovery 100 days after IB-CBT (r = 0.72, P < 0.01 ). Conclusions . The metabolic activity of injected BM predicts the subsequent rate of hematopoietic recovery after IB-CBT, suggesting a pivotal role of the local engraftment in the reconstitution of recipient hematopoiesis.